West Nile virus : forecasting models for a resurging vector-borne disease in Arizona, U.S.A. - Roldan, Josiah Javier (2012)
West Nile Virus (WNV), a vector-borne disease continues to be a serious threat to public health in the United States, particularly in the Southwest region. While all the states in the U.S. experienced a decreasing trend of WNV disease in 2010, the state of Arizona experienced a sharp increase from 20 in 2009 to 166 cases the following year. This dissertation endeavored to develop forecasting models to predict future cases of disease and identify counties with increased propensity for WNV. Furthermore, this study aimed to identify environmental and economic factors that contributed to the increase in WNV cases in Maricopa County, Arizona.